Pengaruh Roasting Kopi Dampit Terhadap Nilai Permeativitas Relatif Kopi Dampit - Septriandi Wira Yoga Yoga; Azam Muzakhim Imamuddin; Moh. Abdullah Anshori; Koesmarijanto Koesmarijanto (Politeknik Negeri Malang, 2021)
The purpose of this study was to design a capacitive sensor system to investigate the effect of Dampit coffee roasting on the relative permeability of coffee. Where this relative permeability value will be used as a reference to determine the level of Dampit coffee roasting. The method used is to design an oscillator circuit, where a capacitive sensor is used as a component of the oscillator. The capacitive sensor is composed of 2 square copper plates with a side length of 10 cm. The distance between the copper plates varies from 2 cm, 3 cm, 4 cm, and 5 cm. The type of oscillator used in this study is an RC oscillator with 4049 CMOS IC. The results of this study indicate that dark roasted coffee has the highest frequency, the largest capacitor value, and the smallest permeability value. Increasing the distance between the copper plates increases the output frequency of the capacitive sensor. The average relative permeativity of dark coffee is 10.92; medium coffee of 12.45; and light coffee of 14.4.